Answer:
66
Step-by-step explanation:
We can write the following equation to solve
Reduce
360 = 5x + 30
5x = 330
x = 66
Answer:
Step-by-step explanation:
2x^2-2x-12
This has solutions of x=3 and x= -2
Rewrite g(x) as x-1
------
4
and then substitute this result for x in f(x) = x^2 - 3x + 3:
f(g(x)) = (x-1)^2 / 4^2 - 3(x-1)/4 + 3.
At this point we can substitute the value 5 for x:
f(g(5)) = (5-1)^2 / 4^2 - 3(5-1)/4 + 3
= 16/16 - 3(4/4) + 3 = 1 - 3 + 3 = 1
Therefore, f(g(5)) = 1.
7X-4=6X-4-X
7X-6X+X=0
2X=0
X=0